Perbandingan Fitur Pada Platform Kuis Terpopuler - Muchammad Chandra Cahyo Utomo; M. Gilvy Langgawan Putra; Dwi Arief Prambudi (STMIK AKBA, 2021)
Because of the COVID-19 outbreak, many schools are applying an online learning activity at home. Because the students are learning at home, the teacher must bring the online exercise or something like that to measure the student’s knowledge. Google Forms, Microsoft Office Forms, Kahoot, and Quizizz can provide online quizzes, but these platforms have their own value point. This study is comparing and mapping the value points of these online quizzes’ platforms. The three main focuses in the comparison, are the variety of questions that can be displayed, the ease of understanding and processing the score of the quiz results, and the limitations in taking the quiz, such as when to do it and the duration of the quiz. Also, this study will give the recommendation of the best platform depending on your needs. Based on the comparison, Google Forms is the most featured platform for various purposes. But if you want to provide a new and enjoyable learning experience for your students, we recommend that you use the Kahoot platform. Keywords: Forms, Google, Kahoot, Microsoft, Quizizz